2003
DOI: 10.1007/s00253-003-1359-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and characteristics of phosphorus-accumulating microbial granules in sequencing batch reactors

Abstract: Phosphorus (P)-accumulating microbial granules were developed at different substrate P/chemical oxygen demand (COD) ratios in the range of 1/100 to 10/100 by weight in sequencing batch reactors. The soluble COD and PO4-P profiles showed that the granules had typical P-accumulating characteristics, with concomitant uptake of soluble organic carbon and the release of phosphate in the anaerobic stage, followed by rapid phosphate uptake in the aerobic stage. The size of P-accumulating granules exhibited a decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 17 publications
3
75
0
Order By: Relevance
“…A similar effect was observed by Lin et al (2003)-the size of granules exhibited a decreasing trend with the decrease in substrate COD/P ratio, while the structure of granules became more compact and denser resulting in lower SVI of microbial granules. The results of the present research confirmed that more compact aggregates are obtained at lower COD/P ratios.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…A similar effect was observed by Lin et al (2003)-the size of granules exhibited a decreasing trend with the decrease in substrate COD/P ratio, while the structure of granules became more compact and denser resulting in lower SVI of microbial granules. The results of the present research confirmed that more compact aggregates are obtained at lower COD/P ratios.…”
Section: Resultssupporting
confidence: 61%
“…The results of the present research confirmed that more compact aggregates are obtained at lower COD/P ratios. It should be mentioned that SVI of the granules in the second run of this study was in the range 50-100 ml/g, reported for non-Paccumulating aerobic granules (Lin et al 2003). Sedimentation of biomass took place after the aeration period; therefore, granules dominated by PAOs contained high amounts of poly-P, which improved settling properties in comparison with GAO-dominated granules.…”
Section: Resultsmentioning
confidence: 94%
“…Formation of the three-dimensional structure of the granules is mediated through a sequence of events [93] and are primarily composed of mixed species microbial consortia held together in a matrix of their own EPS along with other embedded particles [94][95][96][97][98][99]. As in other microbial aggregates, such as biofi lms and biofl ocs, the EPS produced in biogranules are also composed of variable amounts of proteins, polysaccharides, nucleic acids, humic-like substances, lipids and glycoproteins, but the content of EPS in biogranules have been found to be much higher than that of biofl ocs and biofi lms [3].…”
Section: Biogranules and Metal Removalmentioning
confidence: 99%
“…While granules were first reported in an upflow anaerobic sludge blanket bioreactor two decades ago (Lettinga et al, 1980), recent research efforts have been dedicated to the study of aerobic granules (Morgenroth et al, 1997;Beun et al, 1999;Peng et al, 1999;Etterer and Wilderer, 2001;Tay et al, 2001). Aerobic granules cultivated in synthetic wastewater bioreactors have been reported to achieve COD and/or N removal (Tay et al, 2002;Liu et al, 2003;Yang et al, 2003) and, in some cases, P removal (Dulekgurgen et al, 2003;Lin et al, 2003). Aerobic granules can be described as compact and dense aggregates of microbial origin with an approximately spherical external appearance that do not coagulate under reduced hydrodynamic shear and settle significantly faster than conventional activated sludge flocs.…”
Section: Introductionmentioning
confidence: 99%